Entwicklung und Formen von Flexibilität und sozialer Absicherung in den EU-Staaten: Ein Überblick - Julia Bock-Schappelwein (Austrian Institute of Economic Research (WIFO), 2006)
– Tertiarisation, globalisation, technologisation, demographic change and international migration combine to produce changes that affect many spheres of life: new markets are opening up, technological progress accelerates, the usefulness of original education declines, training and ongoing education throughout the various life cycles are gaining in importance, and the composition of the labour supply is getting ever more complex, due to the ageing of the working-age population and the influx of women and non-nationals into the labour market. At the same, habits are changing as well and there is a breakdown in traditional family structures. As a result, labour organisation and labour relations will be redirected and reorientated.
Keywords: 330; Flexicurity Flexibilität; sozialer Absicherung; Soziale Sicherheit; Arbeitsmarktflexibilität; EU-Staaten